IMPEMENTASI KOMUNIKASI EFEKTIF DALAM PEMBELAJARAN ANAK USIA DINI DI TK RUMAH CITTA YOGYAKARTA - AGUS FAISAL, VAVA IMAM (AL-QALAM: JURNAL KEPENDIDIKAN, 2019)
Learning in early childhood is said to be successful if the goal has been reached to its full potential in accordance with the stages of child growth and development. Various ways of applying early childhood learning, especially in the kindergarten environment, have been carried out by the teacher. Given the teacher's central role in maximizing early childhood learning, a form of communication is needed that provides a sense of security and comfort for the child. Effective communication is a form of positive communication as a means of realizing the effectiveness and efficiency of learning. Effective communication is closely related to the delivery of positive words both done by the teacher and the child. actually delivering positive words can provide a sense of security and comfort for children. the comfort and safety of early childhood are needed in facilitating and maximizing the learning process. Whether or not the process of effective communication in early childhood learning depends on the skills and creativity of teachers in language processing, so that the pattern of good relations between teachers and children is maximally established because the child becomes open and does not burden the child. Citta Yogyakarta Kindergarten becomes a research study in implementing effective communication of early childhood. The results of the study include the implementation, impact and supporting factors and obstacles of effective communication implementation in the Citta Rumah Kindergarten.